Teaching English as A Foreign Language in Vocational Schools of New Uzbekistan (Journal of Pedagogical Inventions and Practices, 2022)
In this article, the importance of English as a world language, the benefits of learning and knowing a foreign language, international terms widely used in modern education, words related to the field of production, their application, comparison , using ways by students outside the field of education in their careers.